Pengaruh Informasi Kesetaraan Gender pada Rubrik Swara “Kompas” terhadap Persepsi Pembaca tentang Kesetaraan Gender - Nila Nurlimah (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2005)
The realization of gender equality among members of society haven’t done perfectly yet. We canstill found so many gender inequality cases in our society. Kompas, a leading daily in Indonesia,present articles concerning gender equality as its main topic in their periodical section: “Rubrik Swara”. By giving an interesting title and photo, by presenting a systematic, factual and accurate information, packed with language that easy to comprehend, “Rubrik Swara” would be read by the reader and presumably, influence their perception about gender equality. Research result shows that “Rubrik Swara” of Kompas do influence reader’s perception concerning gender equality.